MARKETING STRATGIES AI & ML IN E- COMMERCE FACEBOOK - SHRISTI PASWAN (International Journal of Educational Excellence and Innovation, 2025)
In the rapidly evolving landscape of e-commerce, the integration of artificial intelligence (AI) and machine learning (ML) technologies has emerged as a pivotal force in shaping marketing strategies. This abstract explores the multifaceted applications of AI and ML in e-commerce marketing and their profound impacts on customer engagement, conversion optimization, and overall business success.AI and ML algorithms empower e-commerce platforms to deliver personalized and dynamic experiences to consumers. Through data analysis and predictive modeling, these technologies enable businesses to segment their target audience more effectively, identify valuable insights from vast datasets, and anticipate consumer behavior with greater accuracy. By leveraging AI-powered recommendation systems, e-commerce companies can offer tailored product suggestions to individual users, thereby enhancing user experience and driving higher conversion rates.Furthermore, AI-driven automation streamlines various marketing processes, including ad targeting, content optimization, and customer support. Automated bidding algorithms optimize advertising spend by adjusting bid amounts in real-time based on performance metrics, while chatbots powered by natural language processing (NLP) provide instant assistance to customers, improving satisfaction and retention